(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Health Information System (HIS) is a combination of hardware, software, process, infrastructure, people and protocol which is developed for management of healthcare data including collection, storage, analysis, decision making and transmission. It supports functional management of a hospital as well as provides an infrastructure that support policy decisions over healthcare data. HIS grown decade by decade starting from 1960 to present era and divided into four generation versions, starting from HIS. V.1.0 to HIS V.4.0. HIS V.4.0 is dedicated for smart medical technology with fog-based computing system including disease-oriented sensing system, IoT, artificial intelligence, high speed internet and advanced internet protocols. Fog Computing is a distributed computing framework and provide an extension to cloud computing. It lies between medical sensor (IoT devices) and cloud datacenters. This paper presents various HIS generations and technologies used in HIS V.4.0. Include review of cloud computing, IoT and Fog computing. Further this paper provides a systematic review of existing research in fog computing with various issue and challenges. Finally, paper describes comparison of fog computing with cloud and edge computing and present discussion, open challenges and recommendation in Fog-based HIS.